In Entrepreneurship Directions for Increasing the Efficient use of Resources (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the development of the economy of our republic, an entrepreneur is primarily a person with a certain level of qualification, who has the authority and responsibility to implement the company's development strategy, such as profit, profitability, and labor productivity. In the article, the interrelationship of the factors of effective use of resources in business enterprises improved.